Front Cover: Delaying Anticancer Drug Delivery by Self‐Assembly and Branching Effects of Minimalist Dendron–Drug Conjugates (Chem. Eur. J. 41/2019). Issue 41 (11th June 2019) - Correard, Florian; Roy, Myriam; Terrasson, Vincent; Braguer, Diane; Estève, Marie‐Anne; Gingras, Marc
Abstract : Self‐assembly of a covalently‐bound lipophilic drug to a dendron for making nanoparticles (Nps) is reported as a proof of concept in nanovectorization. A minimalist structural approach is shown with small PEG‐dendrons (yellow) conjugated to paclitaxel (PTX) which self‐assemble to Nps (beige Nps). They provide anticancer bioactivity (boxing glove) by significantly retarding and targeting intracellular delivery of PTX in 2D and 3D lung cancer cell cultures (red cells). A branching effect of dendrons is crucial, when compared to linear PTX conjugates. More information can be found in the Communication by M.‐A. Estève, M. Gingras, et al. onpage 9586 .